Simplificación de los métodos de los tres momentos y slope deflection para cálculo de vigas continuas y pórticos - Maldonado Vela, Juanito (2000)
This thesis work is a research which consisted of simpliticar the fonnulas estructw·ales of the 3 moments pam continuous beams and Slope Deflection gantries; starting with lUla mathematical law that is "equations convergente.s", coming to the end to a simple procedure for. solve this type of structure. Also be shown that cases specific beams, such as acarteladas beams and lines of influence can be resolved